Methods of Spoken Interaction - Urakovich, Khatamov Ildar (International Journal on Integrated Education, 2023)
In learning Russian language is long, complex process because a learner should know the grammar, phonetic, and other rules to follow. Besides, a learner should have sufficient vocabulary knowledge or be aware of technical terminology in that sphere of expertise. Communication is the main skill of the language learning process as it may provide a learner comprehending the words during the spoken interaction. Furthermore, learners should know the cultural identity of that society for spoken interaction. This paper reveals the methods and activates learners may accomplish and learn for active communication in Russian language.